2019
DOI: 10.1016/j.neubiorev.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive neuroscience of lucid dreaming

Abstract: Lucid dreaming refers to the phenomenon of becoming aware of the fact that one is dreaming during ongoing sleep. Despite having been physiologically validated for decades, the neurobiology of lucid dreaming is still incompletely characterized. Here we review the neuroscientific literature on lucid dreaming, including electroencephalographic, neuroimaging, brain lesion, pharmacological and brain stimulation studies. Electroencephalographic studies of lucid dreaming are mostly underpowered and show mixed results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
151
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 149 publications
3
151
0
Order By: Relevance
“…Lucid dreaming is a dissociated state, which combines aspects of waking and dreaming (Schredl and Erlacher, 2004;Voss et al, 2009;LaBerge et al, 2018). Specifically, it denotes conscious awareness of dreaming during ongoing sleep (Baird et al, 2019). A central characteristic is that experiencers are typically able to signal their lucid state during dream periods using preagreed eye-movement signals (LaBerge, 1980;LaBerge et al, 2018).…”
Section: Introduction Lucid Dreaming Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Lucid dreaming is a dissociated state, which combines aspects of waking and dreaming (Schredl and Erlacher, 2004;Voss et al, 2009;LaBerge et al, 2018). Specifically, it denotes conscious awareness of dreaming during ongoing sleep (Baird et al, 2019). A central characteristic is that experiencers are typically able to signal their lucid state during dream periods using preagreed eye-movement signals (LaBerge, 1980;LaBerge et al, 2018).…”
Section: Introduction Lucid Dreaming Backgroundmentioning
confidence: 99%
“…The concept of lucid dreaming pre-dates modern science as evinced by the work of ancient scholars (Baird et al, 2019). The modern conceptualization of lucid dreaming arose from Frederik van Eeden's examination of his personal dream experiences.…”
Section: Introduction Lucid Dreaming Backgroundmentioning
confidence: 99%
“…3) How the eye movements should be performed: While most LD researchers instruct dreamers to shift their gaze laterally (Mota-Rolim et al, 2008;Voss et al, 2009;Dresler et al, 2012), others instruct to "scan the horizon" from left to right (Dodet et al, 2014). As a way to standardize the PAEM technique, LD researchers can follow the instructions suggested by Baird et al (2019) (adapted from LaBerge et al, 2018, which require asking the dreamer to move the eyes all the way to the left and then to the right (as if looking at each of the ears) through a continuous movement without pausing. 4) When the eye movements should be performed: In addition to during dreaming, this technique could also be practiced during the waking state (with eyes open and closed) before starting the experiment, which constitutes a valuable opportunity for researchers to view the fingerprints of each individual and also provide feedback.…”
Section: Toward a Standardization Of The Paemmentioning
confidence: 99%
“…They also consider that there is a form of consciousness during deep sleep, but that it was not possible to have LD in this state ( Sharma, 2006 ). In fact, studies have found that LD–objectively indicated by the eye movements technique ( Hearne, 1978 ; LaBerge, 1980a , b ; Mota-Rolim, 2020 )–was already described during sleep onset (N1 stage), light sleep (N2), and rapid eye movement (REM) sleep, but not during deep sleep (N3) ( LaBerge et al, 1981a , b ; Stumbrys and Erlacher, 2012 ; Mota-Rolim et al, 2015 ; Baird et al, 2019 ). However, this is still debatable, especially when we consider the Hindu tradition of spiritual sleep: Yoga Nidra.…”
Section: Hinduismmentioning
confidence: 99%
“…EEG recordings showed that during deep sleep, the experimental group (long-term meditators) had greater theta-alpha activity simultaneously with delta activity and lower muscular tonus, when compared to the other groups (short-term and non-practitioners). The authors suggested that transcendental consciousness during sleep is distinct from LD, since the last one occurs almost exclusively during phasic REM and more often during later REM periods ( Mason et al, 1997 ; Baird et al, 2019 ). Finally, studies on Mindfulness Meditation practices also provide empirical support for the possibility of a kind of consciousness in deep sleep ( Tang et al, 2015 ).…”
Section: Hinduismmentioning
confidence: 99%